PENGARUH UKURAN PARTIKEL AMPAS SAGU DALAM PRODUKSI PIGMEN ANGKAK MENGGUNAKAN Monascus purpureus - Alfi Asben; Deivy Andhika Permata (Jurnal Teknologi Pertanian Andalas, 2018)
Angka pigment is one of food colorants that safe to used. It can be produced by subtrate that contain of sago hampas. The objective of the research was to get the appropriate of sago hampas particle size to produce the angkak pigment. The steps to produce of angkak pigment were (a) Preparation of raw materials (sago hampas and rice flour substrate with comparison 1:1 (12.5 : 12.5). This research used  three treatments of sago hampas particle size (40-60 mesh, 60-80 mesh, and >80 mesh) with 3 replications, (b) Preparation of Monascus purpureus culture, (c) Solid state fermentation to produce angkak pigment using M. purpureus. The results of the research showed that the substrate with hampas sago particle size 40-60 mesh produced  the best angkak pigment. The angkak pigment obtain the highest color intensity on λ 400 nm, λ 470 nm, λ 500 nm were 6004, 5110 and 3650 respectively, the highest used starch, antioxidant, toxicity, lovastatin and spore of  M.  purpureus were 11.07%, 45.95%, 1719.86 (LC50), 79 ppm, and 3.4 x 103 CPU/g respectively.